Effects of Training, Job Promotion, and Work Discipline on Employee Performance - Masdino; Ellin Herlina; Weti Kurniawati (PT. Berkah Digital Teknologi, 2026)
Purpose of the study — This study examines the effects of training, job promotion, and work discipline on employee performance at PT Arteria Daya Mulia Cirebon, Indonesia. Research method — This study employed a quantitative explanatory survey involving 94 employees selected from a population of 1,612 employees using the Slovin formula with a 10% margin of error. Data were collected through structured questionnaires using a five-point Likert scale and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression with the assistance of SPSS. Result — The results show that training, job promotion, and work discipline have positive and significant effects on employee performance. The regression model is statistically significant, F(3,90) = 19.666, p < .001, and explains 39.6% of the variance in employee performance. Partially, training has a significant positive effect on employee performance (B = 0.221, p = .001), job promotion has a significant positive effect on employee performance (B = 0.360, p = .005), and work discipline has a significant positive effect on employee performance (B = 0.341, p = .006). Conclusion — The findings indicate that employee performance can be improved through structured training, transparent and merit-based promotion systems, and consistent work discipline mechanisms. These results suggest that manufacturing firms should manage capability development, career advancement, and discipline enforcement as integrated human resource practices to strengthen employee performance.